Analysis of the effectiveness of different play types in the end of game possessions of close EuroLeague matches - Foteinakis, P.; Pavlidou, S.; Stavropoulos, N. (Journal of Human Sport & Exercise, 2024)
End-of-game possessions during the final minutes of a game often have a significant impact on the final result of the match. The purpose of the present study was to analyse the structure and efficacy of possession play types in the last two minutes of the fourth quarter and overtime of EuroLeague close matches and relate them to the result of the game. The offensive play types of 90 EuroLeague games were analysed. 955 end-of-game possessions were analysed and categorized into 11 predefined play types. Sport Scout STA software was used as the observation instrument. The results indicated that the isolation (ISO) play type (23.6%) had the highest frequency, while Hand-Off (0.63%) was the least frequent play type. Cut (CUT) play type was the most effective (82.4%), producing 1.58 Points Per Possession (PPP), followed by PB (69%), and 1.33 PPP. Post Up, ISO, and Spot Up play types were the least effective, producing 0.78-0.98 PPP. Winning teams had longer-lasting possessions compared to defeated teams. Longer-lasting possessions were less effective than possessions that lasted less than 6 seconds. More cooperative play types increased the efficacy of possessions at the end of the game.